Differential effects of three interferon betas on neutralising antibodies in patients with multiple sclerosis: a follow up study in an independent laboratory. Issue 2 (1st August 2002) - Bertolotto, A; Malucchi, S; Sala, A; Orefice, G; Carrieri, P B; Capobianco, M; Milano, E; Melis, F; Giordana, M T
Abstract : Objective: To evaluate the incidence and the prevalence of neutralising antibodies (NABs) to three interferon beta (IFNβ) products in patients with multiple sclerosis (MS). Methods: Sera were tested from 125 patients with relapsing-remitting MS. Patients were treated with IFNβ-1b (Betaferon, n = 29) 8 MIU subcutaneously every other day, IFNβ-1a (Avonex, n = 44) 30 μg intramuscularly once weekly, or IFNβ-1a (Rebif, n = 36) 22 μg subcutaneously three times weekly for 6 to 18 months. An additional 16 patients were treated with Rebif 22 μg intramuscularly once or twice weekly. NABs were assessed using the cytopathic effect assay before treatment and every three months during treatment. Patients with two or more consecutive positive samples were considered to be persistent NAB positive (NAB+). Results: At baseline, no patients were NAB+. NABs developed during the first three months of treatment and continued to develop until month 18. Over 18 months of treatment, the risk of being persistent NAB+ was 31% for Betaferon, 15% for Rebif, and 2% for Avonex (Betaferon versus Avonex, p = 0.001; Betaferon versus Rebif, p = 0.19; Rebif versus Avonex, p = 0.04). In all patients with one or more NAB+ samples, the risk of becoming NAB+ was 38% for Betaferon, 18% for Rebif, and 7% for Avonex (Betaferon versus Avonex, p = 0.0007; Betaferon versus Rebif, p = 0.10; Rebif versus Avonex, p = 0.07). At month 18, the prevalence of persistent NAB+ patients was 31.6% for Betaferon, 18.7% for Rebif, and 4% for Avonex. Numbers of NAB+ patients observed were similar with intramuscular Rebif and with subcutaneous Rebif. Conclusion: The three IFNβ preparations have different degrees of immunogenicity, with Betaferon producing the highest incidence of NABs and Avonex the lowest. These differences should be considered by neurologists when selecting treatment for their patients with MS because NABs can reduce both bioavailability and clinical efficacy of IFNβ.